Association of environmental and behavioral factors with leptospirosis seroconversion a comparison of Bayesian and Frequentist approaches to estimation - Peralta, Cheryl R. 1975- (2014)
Background: In the analysis of leptospirosis studies, there is a need to properly account for ecologic and individual level variables that may lead to leptospirosis infection, as well as the use of prior information in order to arrive at more valid estimates of association. Objectives: This study aims to 1) Develop composite indexes of environmental and behavioral factors for leptospirosis; 2) Determine the association between risky behaviors and leptospirosis seroconversion; 3) Determine the association between household proximity risk factors to leptospirosis seroconversion; 4) Determine the association between household flood risk and leptospirosis seroconversion; and 5) Qualitatively compare the parameter estimates and credible intervals obtained using hierarchical empirical Bayes regression modeling with the usual practice of traditional logistic regression and hierarchical regression modeling. Methods: This study is a secondary data analysis of the findings of cumulative nested case-control study. A total of 45 cases and 257 controls participated in the study. Blood samples from eligible participants were screened using Lepto IgG ELISA. Environmental and behavioral exposures were determined using a structured questionnaire directly administered through interviews. The presence of household risk factors, such as cracked walls and cracked ceilings, was validated by direct observation done by the interviewer. House elevation was determined using the Google Earth software Results: Four indexes were developed for this study: Household proximity risk index, household rat infestation index, leptospirosis risky behaviors index, and individual flood risk index. Though the results did not reach statistical significance, there seems to be an association between risky behaviors and leptospirosis seroconversion, conditional on gender, individual flood experience, rat presence and unconsumed pet food in the household, and house elevation above sea level. House elevation, as an indicator of household flood risk is associated with leptospirosis seroconversion but the data did not provide evidence that household proximity to sewers, disposal sites, river/creek, and market increase risk. Conclusion: Given the data, the priors, and the model, risky behaviors and household flood risk seem to be associated with leptospirosis seroconversion, but there seems to be no evidence that household proximity risk factors are associated with the infection. Hierarchical Empirical Bayes estimates are deemed more appropriate for analysis of leptospirosis studies involving ecologic and individual level variables because while it allows for the integration of prior information, it likewise provides a more realistic interpretation of interval estimates compared to the frequentist approach